Explaining Consumers' Impulse Buying in Live Streaming Marketing Through Perceived Trust and Perceived Value - Najwa Aulia Yuzwanisa; Ananda Setiawan; Monry Fraick Nicky Gillian Ratumbuysang; Muhammad Rahmattullah (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
The rapid growth of live-streaming commerce has transformed online shopping behavior by creating interactive purchasing environments that encourage impulse buying. This study aims to examine the effects of streamer characteristics, online comments, and promotional time limits on impulse buying behavior through perceived trust and perceived value among consumers in South Kalimantan, Indonesia. A quantitative approach was employed, and data were collected through an online questionnaire from 270 respondents who had watched and made purchases through live-streaming commerce. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that streamer characteristics positively and significantly influence both perceived trust and perceived value, while promotional time limits positively and significantly influence perceived value. Furthermore, perceived trust and perceived value positively and significantly influence impulse buying behavior. In contrast, online comments do not have a significant effect on either perceived trust or perceived value. These findings suggest that streamer characteristics and promotional time limits play an important role in shaping consumers' psychological responses and impulse buying behavior in live-streaming commerce. This study contributes to the Stimulus Organism Response (SOR) literature and provides practical implications for businesses in developing more effective live-streaming marketing strategies.